2016
DOI: 10.1002/trtr.1489
|View full text |Cite
|
Sign up to set email alerts
|

Text-Based Writing Assignments for College Readiness

Abstract: Research shows that cognitively demanding text‐based writing assignments increase students' reading comprehension skills and analytic writing competencies. In this article, we describe the steps that upper‐elementary grade teachers can take to develop cognitively demanding assignments that build these higher‐level literacy skills and put students on the path to college readiness. Specifically, we discuss features of texts, both fiction and nonfiction, that provide grist for students to grapple with in their wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It is known that writing is a critical aspect of student learning as it fosters deeper insight and understanding of disseminated information as well as the integration of knowledge from distinct contexts (Emig, 1977). Studies have shown that writing assignments increase students' reading comprehension skills and analytic writing competencies (Matsumura, Wang, & Correnti, 2016). This exemplifies the importance of writing as a critical pedagogical tool.…”
Section: Introductionmentioning
confidence: 96%
“…It is known that writing is a critical aspect of student learning as it fosters deeper insight and understanding of disseminated information as well as the integration of knowledge from distinct contexts (Emig, 1977). Studies have shown that writing assignments increase students' reading comprehension skills and analytic writing competencies (Matsumura, Wang, & Correnti, 2016). This exemplifies the importance of writing as a critical pedagogical tool.…”
Section: Introductionmentioning
confidence: 96%
“…Analytic text‐based writing is critical to college readiness (CCSSO, 2010). This form of writing requires students to generate new insights about a complex text, express higher‐level thinking, and justify their claims with reasons and evidence (Matsumura et al, 2016). In addition to being an important skill to master in itself, analytic writing bolsters students’ reading and writing skill development (Graham & Hebert, 2011; Matsumura et al, 2015) and deepens knowledge of subject‐matter content (Graham et al, 2020).…”
mentioning
confidence: 99%
“…In this teaching tip, we help teachers provide written feedback to support upper elementary students' higher level thinking about texts in writing. In previous articles, we discussed how to choose texts and prompts that can engage students deeply with the meaning of text(s) (Matsumura, Wang, & Correnti, 2016) as well as ways to support students to use text evidence effectively in their writing (Wang, Matsumura, & Correnti, 2017). In this teaching tip, we focus on student thinking in writing.…”
mentioning
confidence: 99%